2006
DOI: 10.1021/np060147p
|View full text |Cite
|
Sign up to set email alerts
|

Ashwagandhanolide, a Bioactive Dimeric Thiowithanolide Isolated from the Roots of Withania somnifera

Abstract: A new dimeric withanolide, ashwagandhanolide (1), was isolated from the roots of an Ayurvedic medicinal herb, Withania somnifera. A detailed spectroscopic evaluation revealed its identity as a dimer with an unusual thioether linkage. Compound 1 displayed growth inhibition against human gastric (AGS), breast (MCF-7), central nervous system (SF-268), colon (HCT-116), and lung (NCI H460) cancer cell lines, with IC50 values in the range 0.43-1.48 microg/mL. In addition, it inhibited lipid peroxidation and the acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
52
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 82 publications
(58 citation statements)
references
References 12 publications
0
52
1
Order By: Relevance
“…Indeed, component 32, detected in the W. somnifera extract by LC-MS n analysis ( Table 1, Fig. 5), showed mass spectral data consistent with the dimeric thiowithanolide, ashwagandhanolide, a compound reported to inhibit cell proliferation in various tumor cell lines (Subbaraju et al, 2006).…”
Section: Lc-ms N Analysismentioning
confidence: 59%
See 2 more Smart Citations
“…Indeed, component 32, detected in the W. somnifera extract by LC-MS n analysis ( Table 1, Fig. 5), showed mass spectral data consistent with the dimeric thiowithanolide, ashwagandhanolide, a compound reported to inhibit cell proliferation in various tumor cell lines (Subbaraju et al, 2006).…”
Section: Lc-ms N Analysismentioning
confidence: 59%
“…There is also evidence of neuroprotection by withanolide A, withanoside IV, and withanoside VI, steroidal derivatives isolated from a root extract of One in vitro study showed an interesting finding in which W. somnifera root extract significantly and dose-dependently increased the percentage of cells with neurites in human neuroblastoma SK-N-SH cells (Tohda et al, 2000). However, one observation in our study was that at high concentrations (> 100 µg/mL), the aqueous extract exhibited cytotoxic and perhaps anti-proliferative properties against the dPC12 cell line, (Subbaraju et al, 2006;Stan et al, 2008). Indeed, component 32, detected in the W. somnifera extract by LC-MS n analysis ( Table 1, Fig.…”
Section: Lc-ms N Analysismentioning
confidence: 65%
See 1 more Smart Citation
“…Withaferin A (1), its diacetate, viscosalactone B (505), compound 6, and ashwagandhanolide (78) were the most active (IC 50 range 0.5-1 mM) and comparable in potency to a reference compound, adriamycin (47,240). Compound 78 also inhibited lipid peroxidation and the activity of the enzyme cyclooxygenase-2 in vitro.…”
Section: Cytotoxicitymentioning
confidence: 99%
“…Among the reported withanolides, withaferin A (WA) (16) (as seen in Fig. 1) and ashwagandhanolide (17), obtained from the leaves and roots, respectively, are well-known potent secondary metabolites of W. somnifera and are reported to possess anticancer properties. Antiproliferative, antimetastatic, antiangiogenic, anti-invasive and proapoptotic activities of withanolides have been reported, with the underlying mechanism found to be associated with the suppression of nuclear factor (NF)-κB and NF-κB-regulated gene products (18).…”
Section: Introductionmentioning
confidence: 99%